The complete mitochondrial and plastid genomes of Rhododendron simsii, an important parent of widely cultivated azaleas - Jie Xu; Hang Luo; Shuai Nie; Ren-Gang Zhang; Jian-Feng Mao (Mitochondrial DNA. Part B. Resources, 2021)
The genus Rhododendron of the heather family (Ericaceae) is well known and widely cultivated for their highly ornamental value. The most widely cultivated Rhododendron species is Rhododendron simsii (Indoor azalea). In this study, we assembled the complete linear mitochondrial genome (GenBank accession number MW030508) and quadripartite plastid genome (GenBank accession number MW030509). The mitochondrial genome is 802,707 bp in length with containing 53 unique genes (33 protein-coding, 17 tRNA, and 3 rRNA genes), while the 152,214 bp long plastid genome is smaller and containing 105 unique genes (4 rRNA, 26 tRNA, and 75 protein-coding genes). Phylogenetic analysis showed that the same species relationship with APG system as well as the low supports of branches which is the common characteristic of resolved Ericales phylogenetics.